2021
DOI: 10.1016/j.breast.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary view of mastectomy and breast reconstruction: Understanding the challenges

Abstract: The current review paper was written in collaboration with breast cancer surgeons from the European Breast Cancer Research Association of Surgical Trialists (EUBREAST), a breast pathologist from the Danish Breast Cancer Group (DBCG), and representatives from the European SocieTy for Radiotherapy & Oncology (ESTRO) breast cancer course. Herein we summarize the different mastectomies and reconstruction procedures and define high-risk anatomical areas for breast cancer recurrences, to further specify the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Perceived risks such as a fear of developing a second breast cancer, a historical belief that mastectomy is a safer option, possible avoidance of long-term breast cancer surveillance imaging, and the inconvenience of daily radiotherapy treatments may all have contributed to increasing mastectomy rates, which is of concern [53,[65][66][67]. Nevertheless, it is important to note that different mastectomy and reconstruction techniques may lead to various amounts of remaining breast glandular tissue, potentially increasing the risk of breast cancer residual disease or recurrence [68].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived risks such as a fear of developing a second breast cancer, a historical belief that mastectomy is a safer option, possible avoidance of long-term breast cancer surveillance imaging, and the inconvenience of daily radiotherapy treatments may all have contributed to increasing mastectomy rates, which is of concern [53,[65][66][67]. Nevertheless, it is important to note that different mastectomy and reconstruction techniques may lead to various amounts of remaining breast glandular tissue, potentially increasing the risk of breast cancer residual disease or recurrence [68].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prior breast irradiation may increase complications and jeopardize cosmesis of subsequent breast reconstruction [ 8 ]. The optimal timing and technique of breast reconstruction in patients who need chest-wall irradiation (PMRT) is controversial [ 8 , 9 ], and it has been repeatedly reported that chest wall irradiation is associated with inferior reconstructive results. Thus, in patients undergoing implant-based reconstruction, PMRT increases rates of infections, capsular contracture, implant loss and overall reconstructive failure requiring revision surgeries, whereas in patients undergoing autologous reconstruction, PMRT has been associated with fibrosis, distortion of breast shape, volume loss, and fat necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand that the risk of residual glandular tissue and/or disease relies in the nature of the NSM/SSM, regardless of surgeon expertise [9,12,13]. To preserve the native breast skin, the surgeons need to separate the mammary gland from the subcutaneous fat at the level of the superficial fascia (the ventral sheet of the pectoral fascia).…”
mentioning
confidence: 99%
“…To preserve the native breast skin, the surgeons need to separate the mammary gland from the subcutaneous fat at the level of the superficial fascia (the ventral sheet of the pectoral fascia). This fascia is described as a definite but very delicate and discontinuous structure that may be challenging to identify [13,14]. Notably, limits of anatomic extension of the fibroglandular tissue may be imprecise and show substantial variation from a very definite distinction between breast tissue and subcutis or breast glands being intertwined with skin adnexa [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation